The Rich Man - Homel, Gene (Labour / Le Travail, 2008)
The article reviews the book, "The Rich Man," by Henry Kreisel.
Keywords: BOOKS -- Reviews; Fiction; KREISEL, Henry; RICH Man, The (Book); RICH people